2023
DOI: 10.3390/medicina59030554
|View full text |Cite
|
Sign up to set email alerts
|

Atherosclerotic Cardiovascular Disease in Inflammatory Bowel Disease: The Role of Chronic Inflammation and Platelet Aggregation

Abstract: Background and Objectives: Atherosclerosis is one of inflammatory bowel disease’s most significant cardiovascular manifestations. This research aimed to examine the relationship between biochemical, haemostatic, and immune parameters of atherosclerosis and ulcerative colitis patients and its relationship to platelet aggregation. Materials and Methods: A clinical, observational cross-sectional study was performed, during which the tested parameters were compared in the experimental and control groups. The patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 79 publications
0
2
0
Order By: Relevance
“…In vitro studies have shown that RC can be directly taken up by macrophages (Nakajima et al., 2006 ) and that RC particles possess a larger size and a higher cholesterol‐carrying capacity than LDL‐C particles (Salinas & Chapman, 2020 ); therefore, it has a greater atherogenic capacity when it enters the endothelium. Other factors such as inflammation (Bernelot Moens et al., 2017 ; Lugonja et al., 2023 ; Varbo et al., 2013 ), induction of endothelial dysfunction (Liu et al., 2009 ), and vascular endothelial injury (Packard, 2022 ) may also be potential pathogenic mechanisms of RC.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies have shown that RC can be directly taken up by macrophages (Nakajima et al., 2006 ) and that RC particles possess a larger size and a higher cholesterol‐carrying capacity than LDL‐C particles (Salinas & Chapman, 2020 ); therefore, it has a greater atherogenic capacity when it enters the endothelium. Other factors such as inflammation (Bernelot Moens et al., 2017 ; Lugonja et al., 2023 ; Varbo et al., 2013 ), induction of endothelial dysfunction (Liu et al., 2009 ), and vascular endothelial injury (Packard, 2022 ) may also be potential pathogenic mechanisms of RC.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies found a correlation between thrombocytosis and atherosclerosis [ 12 , 13 ]. Aside from high platelet count, patients have also been found to have increased platelet activation and aggregation, which also increases the tendency for thrombosis in patients with UC [ 14 , 15 ]. There is evidence that treatment with adalimumab can also contribute to thromboembolic events [ 16 ].…”
Section: Introductionmentioning
confidence: 99%